2003
DOI: 10.1248/cpb.51.230
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetes Effect of Zn(II)/Carnitine Complex by Oral Administration.

Abstract: A novel bis(L-carnitinato)Zn(II) complex, Zn(car) 2 Cl 2 , was prepared, and its insulinomimetic and antidiabetic activities were examined. The complex showed a tendency to lower the high blood glucose levels of KK-A y mice with type 2 diabetes mellitus when given by oral administration at a dose of 20 mg Zn/kg body weight for 16 d. In addition, the complex improved glucose tolerance ability when examined by the oral glucose tolerance test (1 g glucose/kg body weight).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…One reported that oral administration of a zinc-carnitine complex lowered the high blood glucose levels and improved glucose tolerance in KK-A y mice with type 2 diabetes [14]. A more recent study [15] examined the effects of carnitine in liver-specific carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1)-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…One reported that oral administration of a zinc-carnitine complex lowered the high blood glucose levels and improved glucose tolerance in KK-A y mice with type 2 diabetes [14]. A more recent study [15] examined the effects of carnitine in liver-specific carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1)-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…In genetically obese (ob/ob) mice, 20 mM ZnCl 2 in the drinking water for eight weeks reduced fasting plasma glucose levels by 21% and decreased fasting plasma insulin levels by 42%, as well as improving glucose tolerance, as tested by glucose load [29]. Very recently, a number of zinc complexes have been tested, both in vitro and in vivo, as ''insulinomimetics'' [30,31]. Among the complexes tested was bis(maltolato)zinc(II), Zn(ma) 2 [32], which normalized blood glucose levels in KKA y mice, a model of type 2 diabetes, when given i.p., 4.5 mg Zn kg À1 (69 lmol Zn) for 2 d followed by 2.0 mg Zn kg À1 (31 lmol Zn) for 12 d. In humans, supplementation with zinc, an essential trace element, had an unexpected negative impact on diabetic control [32].…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] These results demonstrate that following chronic oral gavage, [ZnA C H T U N G T R E N N U N G (tpps)] has a higher normoglycemic activity in KKA y mice than ZnSO 4 …”
Section: Resultsmentioning
confidence: 97%